(untitled) (Revista Brasileira de Plantas Medicinais, 2000)
A micropropagation protocol for large scale production of Salix humboldtiana Hild. was carried out using both, explants excised from adult plants and from cloned plantlets. Either shoot proliferation or root induction were influenced by the source of explant used. MS medium supplemented with 2,3 μM kinetin enhanced shoot production while half-strength MS medium added with 5.3 μM NAA enhanced rooting. During the acclimatization process, irrigation with 0.005% (v/v) ampicillin solution was essential for plant maintenance.